Clinical validation of atlas-based auto-segmentation of pelvic volumes and normal tissue in rectal tumors using auto-segmentation computed system. (November 2013) - Gambacorta, Maria Antonietta; Valentini, Chiara; Dinapoli, Nicola; Boldrini, Luca; Caria, Nicola; Barba, Maria Cristina; Mattiucci, Gian Carlo; Pasini, Danilo; Minsky, Bruce; Valentini, Vincenzo
Abstract Purpose. To evaluate in two different settings – clinical practice and education/training – the reliability, time efficiency and the ideal sequence of an atlas-based auto-segmentation system in pelvic delineation of locally advanced rectal cancer. Methods. Fourteen consecutive patients were selected between October and December 2011. The images of four were used as an atlas and 10 used for validation. Two independent operators participated: a Delineator to contour and a Reviewer to perform an independent check (IC). The CTV, pelvic subsites and organs at risk were contoured in four different sequences. These included A: manual; B: auto-segmentation; C: auto-segmentation + manual revision; and D: manual + auto-segmentation + manual revision. Contouring was performed by the Delineator using the same planning CT. All of them underwent an IC by a Reviewer. The time required for all the contours were recorded and overlapping evaluation was assessed using a Dice coefficient. Results. In the clinical practice setting there have been 13 minutes time saved between sequences A versus sequences B (from 38 to 25 minutes, p = 0.002), a mean Dice coefficient in favor of sequences A for CTV and all subsites (p = 0.0195). In the educational/training setting there have been 35.2 minutes time saved between sequences C and D 8 (from 73.1 min to 37.9 min, p = 0.002). Conclusion. The preliminary data suggest that the use of an atlas-based auto-contouring system may help improve efficiencies in contouring in the clinical practice setting and could have a tutorial role in the educational/training setting.